V. Ya. Bryusov and N.Ya Bryusova on the Pages of the Weekly «Music» (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-171-179At the end of  November 1910 a new musical weekly «Music» was founded, the editor-publisher of which was V.V. Derzhanovsky. He allotted a significant place on the pages of the publication to the creativity of Russian Symbolists: there were published announcements and reviews of the Symbolists published in the publishing houses «Scorpio», “Musaget”, “Grif”, their poetic texts. Of particular interest to the publisher of “Music” was the literary work of V.Ya. Bryusov, as well as the activities of his closest circle, in particular, the poet’s sister, N. Ya. Bryusova.Keywords: V.Ya. Bryusov, N. Ya. Bryusova, V.V. Derzhanovsky, S.N. Vasilenko, L. Saminsky, “Music” weekly.